Spirituality and Leadership - Iona Gherman, Tatiana (2012)
We reflect then on the meaning of the “Catholic social tradition”, trying to provide a deeper and objective understanding of the notion of Catholic values. We can integrate concepts from moral philosophy, psychology and Catholic religion (see Figure 1 and Figure 2). In other words, we want to show how other perspectives can be integrated, that is based on Kant, Hegel or Sartre, and reaching to the Catholic values, showing in a practical manner the universality of these values. The purpose of all this discussion would be to address the basic question about the meaning of life and to emphasize the profound desire of the human being to discover it. The ability to answer such a question will enable the man to determine his position in front and towards each of the problems of his daily existence. Search for meaning of life is not just a matter of philosophy, but a daily elementary necessity.